Healthy Life-Years Lost and Excess Bed-Days Due to 6 Patient Safety Incidents: Empirical Evidence From English Hospitals. Issue 2 (February 2017) - Hauck, Katharina D.; Wang, Shaolin; Vincent, Charles; Smith, Peter C.
Abstract : Background: There is little satisfactory evidence on the harm of safety incidents to patients, in terms of lost potential health and life-years. Objective: To estimate the healthy life-years (HLYs) lost due to 6 incidents in English hospitals between the years 2005/2006 and 2009/2010, to compare burden across incidents, and estimate excess bed-days. Research Design: The study used cross-sectional analysis of the medical records of all inpatients treated in 273 English hospitals. Patients with 6 types of preventable incidents were identified. Total attributable loss of HLYs was estimated through propensity score matching by considering the hypothetical remaining length and quality of life had the incident not occurred. Results: The 6 incidents resulted in an annual loss of 68 HLYs and 934 excess bed-days per 100, 000 population. Preventable pressure ulcers caused the loss of 26 HLYs and 555 excess bed-days annually. Deaths in low-mortality procedures resulted in 25 lost life-years and 42 bed-days. Deep-vein thrombosis/pulmonary embolisms cost 12 HLYs, and 240 bed-days. Postoperative sepsis, hip fractures, and central-line infections cost <6 HLYs and 100 bed-days each. Discussion: The burden caused by the 6 incidents is roughly comparable with the UK burden of Multiple Sclerosis (80 DALYs per 100, 000), HIV/AIDS and Tuberculosis (63 DALYs), and Cervical Cancer (58 DALYs). There were marked differences in the harm caused by the incidents, despite the public attention all of them receive. Decision makers can use the results to prioritize resources into further research and effective interventions. Abstract : Supplemental Digital Content is available in the text.